2004
DOI: 10.1128/jvi.78.4.1936-1944.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Inhibition of Spreading of In Vitro Infection and Imbalance of Viral Protein Accumulation at Low pH in Viral Hemorrhagic Septicemia Rhabdovirus, a Salmonid Rhabdovirus

Abstract: The inhibition of viral hemorrhagic septicemia rhabdovirus (VHSV) in vitro infection by pHs of <7 (low pH) has been previously reported. Nevertheless, the details of the mechanism underlying this effect remain obscure. We present evidence showing that low-pH inhibition occurs during a viral postadsorption step. Thus, while VHSV bound, replicated within single cells, and presented its G protein on the membranes of infected cells at both low and physiological pHs, both cell-to-cell spreading of infection (as est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
0
14
0
2
Order By: Relevance
“…In vitro, those antibody-armed NK-like effector cells could have attached to VHSV-infected target cells. Since it has been demonstrated that VHSV-infected cells incorporate G protein into their cell membrane [54], this attachment could result in ADCC. Therefore the question of ADCC should be a subject of further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, those antibody-armed NK-like effector cells could have attached to VHSV-infected target cells. Since it has been demonstrated that VHSV-infected cells incorporate G protein into their cell membrane [54], this attachment could result in ADCC. Therefore the question of ADCC should be a subject of further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In all these cases, the change in conformation at physiological pH at position 140 or 433 (as estimated by binding of MAb C10) and 235 (as estimated by binding of MAb 2F1A12) did not abolished fusion. The increase in the binding of MAbs C10 and 2F1A12 to wild-type pG at low pH (31) might indicate that the conformation at low pH required for fusion is less strongly affected by these mutations. Figure 1 shows that the mutants with fusion activity at position P79 or L85 (around position 80) and position T135 (around position 140) and the mutants resistant to neutralization by MAb C10 (21) were mapped at positions around either amino acid 80 or 140, the two locations around which the number of amino acid changes in 22 isolates of VHSV was the greatest.…”
Section: Discussionmentioning
confidence: 99%
“…32 The use of tamponed water with high pH facilitated the reproducibility of the pH-sensitive infection with VHSV. 33 All the experimental protocols were performed with the approval of the Ethics Committee at INIA.…”
Section: Zebrafish Maintenancementioning
confidence: 99%